SIGGRAPH Asia 2015 Technical Briefs 2015
DOI: 10.1145/2820903.2820917
|View full text |Cite
|
Sign up to set email alerts
|

Region-based painting style transfer

Abstract: In this paper, we present a novel method for creating a painted image from a photograph using an existing painting as a style source. The core idea is to identify the corresponding objects in the two images in order to select patches more appropriately. We automatically make a region correspondence between the painted source image and the target photograph by computing color and texture feature distances. Next, we conduct a patch-based synthesis that preserves the appropriate source and target features. Unlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Yamaguchi et al [3] created a system that automatically converted live-action images into an animation style in order to reduce the burden of hand-drawn frames. The system performs style transformation by segmenting regions of the image such as the sky and ground, and then transcribes the corresponding textures.The results showed that the system reflected the style of the animated image better than the conventional method, but there was a point where some textures could not be transferred due to the lack of corresponding parts.…”
Section: Related Workmentioning
confidence: 99%
“…Yamaguchi et al [3] created a system that automatically converted live-action images into an animation style in order to reduce the burden of hand-drawn frames. The system performs style transformation by segmenting regions of the image such as the sky and ground, and then transcribes the corresponding textures.The results showed that the system reflected the style of the animated image better than the conventional method, but there was a point where some textures could not be transferred due to the lack of corresponding parts.…”
Section: Related Workmentioning
confidence: 99%
“…Constructing closed area correspondences between two raster images has been thoroughly investigated [20]. In the field of reference-based colorization of line drawings, Sato et al [21] utilize the positional and connection relationships of closed areas in the keyframes to construct their correspondence.…”
Section: Closed Area Correspondencementioning
confidence: 99%